Repair of high-flow cerebrospinal fluid leak by combined artificial dura plug and free mucosal flap in 15 cases - Zhang, Hengsen; Li, Duoduo; Liu, Zhitong; Chen, Bin; Limchoopornwikul, Pasut; Wang, Yibao; Wang, Yong (Frontiers in Surgery, 2025)
BackgroundIn the endoscopic endonasal approach skull base surgery repair and reconstruction of the base of the skull is a critical step. Free mucosal flaps are primarily used to repair low-flow cerebrospinal fluid (CSF) leaks, whereas they are not adequate in the face of high-flow CSF leaks. We propose a modified approach-termed the “Fishing method”-which utilizes free mucosal flaps in combination with absorbable sutures and an artificial dura to reverse-plug the defect, to repair high-flow CSF leaks with a clear point of origin.ObjectiveTo investigate the application of the “Fishing method” to repair high-flow CSF leaks caused by large diaphragma sellae rupture and small dura leak that occur unexpectedly during endoscopic endonasal sellae area surgery.MethodsA retrospective analysis was conducted including 15 patients with unexpected intraoperative high-flow cerebrospinal fluid leaks. The “Fishing method” was applied to reconstruct and repair the skull base in these patients, and the results were evaluated.ResultsIn 10 cases of large diaphragma sellae rupture that occurred during pituitary adenomas resection, all 10 patients were successfully repaired in a single operation using the “Fishing method”, with no cerebrospinal fluid nasal leakage (100%); in 5 cases of small dura ruptures that occurred during chordoma resection, 4 patients underwent successful repair in a single operation, with no cerebrospinal fluid nasal leakage occurring in 80% of cases, resulting in an overall success rate of 93.3%.ConclusionThe “Fishing method” is a reliable technique for skull base reconstruction and serves as an effective solution for high-flow CSF leaks caused by unexpected large diaphragma sellae rupture or a small dura leak occurring intraoperatively.